Hyperexcitability of the Central Nervous System in Children with Chronic Pain: A Systematic Review. Issue 12 (2nd January 2018) - Pas, Roselien; Ickmans, Kelly; Van Oosterwijck, Sophie; Van der Cruyssen, Kelly; Foubert, Anthe; Leysen, Laurence; Nijs, Jo; Meeus, Mira
Abstract: Objective: Hyperexcitability of the central nervous system plays an important role in the development and maintenance of chronic pain in adults. This knowledge has led to improved treatment strategies within this population. In children, however, research on the presence of central hyperexcitability is scarce. To further investigate this topic in children with chronic pain, there is a need for a clear literature overview. Design: Systematic review. Methods: The literature search was performed using the electronic databases PubMed and Web of Science. An article was considered eligible if it included children (age two to 12 years) diagnosed with chronic pain. Articles had to report original research outcomes related to central hyperexcitability, and a comparison with a healthy control group was necessary. Characteristics of the study sample, the assessment, and conclusions regarding central hyperexcitability were extracted from each included article. Results: Twelve case-control studies were included with moderate to good methodological quality (510 children with chronic pain and 670 healthy controls). After summarizing the articles' results on indices of central hyperexcitability, we concluded that secondary hyperalgesia might be present in children with recurrent abdominal pain, juvenile fibromyalgia, and juvenile idiopathic arthritis. Preliminary evidence exists for altered cortical nociceptive processing in children with migraine and recurrent abdominal pain. Conclusion: Based on the results of this review, central hyperexcitability might be present in in several pediatric chronic pain conditions. Further research on other manifestations of central hyperexcitability (e.g., bottom-up and top-down mechanisms and nociceptive brain changes) is necessary to provide firm evidence about its presence in children with chronic pain.